Social Harmonization in The Sadranan Tradition: Case Study Dk. Mulwo, Ds. Muruh, Gantiwarno District, Klaten Regency - Hery Riyanto (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
One form of Javanese culture is the sadranan tradition. The sadranan tradition is a tradition that is still going on today. Sadranan is carried out as a form of gratitude to True Source. Sadranan is usually performed in the month of shaban (ruwah). One of the communities that still routinely carry out the sadranan tradition is the community in Mulwo. The pluralism that exists in the Mulwo community is not a barrier to the implementation of the sadranan tradition. The differences that exist in the Mulwo community create social harmony. The values contained in social harmony in the sadranan in Mulwo are illustrated in the entire series of sadranan events which include; Pre-sadranan, sadranan, and post-sadranan. This research is qualitative research with descriptive-analysis data analysis methods. This type of research is field research with a sociological approach to reveal more deeply the sadranan tradition of creating social harmony in the Mulwo dukuh community. The data in this study is the sadranan tradition in Dukuh Mulwo as primary data, and secondary data sources include data obtained from books, articles, theses and documents related to the research. Observation, interviews, and documentation are used to carry out data collection techniques.